Magnetophotonics : from theory to applications - Levy, Miguel; Baryshev, Alexander V.; Inoue, Mitsuteru (Springer Series in Materials Science, 2013)
This book merges theoretical and experimental works initiated in 1997 from consideration of periodical artificial dielectric structures comprising magneto-optical materials. Modern advances in magnetophotonics are discussed giving theoretical analyses and demonstrations of the consequences of light interaction with non-reciprocal media of various designs. This first collection of foundational works is devoted to light-to-artificial magnetic matter phenomena and related applications. The subject covers the physical background and the continuing research in the field of magnetophotonics.